Efektivitas Model Evaluasi CIPP dalam Program Pendidikan: Kajian Literatur Sistematis - Riawan, I Made Oka; Citariani, Ni Made; Lokasanti, I Ketut (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2025)
This study aims to systematically examine the effectiveness of the CIPP (Context, Input, Process, Product) evaluation model in various educational programs. A Systematic Literature Review (SLR) method was employed to identify, evaluate, and synthesize relevant findings from previous studies. Data were collected from various national and international journal databases, with inclusion criteria covering publications from 2022 to 2025, using keywords such as